Generation of Thermoelectric Power Utilizing Alternative Sources of Energy (International Journal of Innovative Research in Engineering & Management, 2023)
n latest days’ environmental issues such  as pollution, particularly global warming and energy  resource constraints, has led in extensive research into  new electrical power generating methods. Thermoelectric  power generators have emerged as an intriguing  prospective green technology owing to its many  advantages. Thermoelectric power production has a  potential application in the direct conversion of waste heat energy to electrical power, when the cost of the  thermal energy source is not taken into consideration. The  adoption of this alternative green technologies for directly  converting waste-heat energy into electrical power would  also improve the overall efficiency of energy conversion  systems. This article offers a viewpoint on the basic  principles of thermoelectric power production, as well as  a research and discussion of contemporary thermoelectric  power generation with intriguing and practical uses of  waste-heat electricity.
Keywords: Energy; Electrical Power; Green Technology; Thermoelectric Power; Thermoelectric Power Generation